New Approach to Liberia Population and Housing Census : From Traditional Based to Combined Approach - Williams, G Alex M (2020)
This thesis aims to define the future of population statistics in Liberia by providing a roadmap on how Liberia could leverage on the experiences of other nations to transition from a traditional-based census to a combined approach. It is the view of the author that the Combined Census approach would not only improve the quality of population statistics in Liberia but is also a cost-saving method for Liberia, especially as a poor and underdeveloped nation.